2017
DOI: 10.1002/ange.201706517
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Red‐Emissive Organic Crystals with Amplified Spontaneous Emissions Based on a Single Benzene Framework

Abstract: Red-emissive fluorophores generally consist of large p-extended systems and thus encounter the problem of serious fluorescence quenching in the solid state.Aseries of structurally simple compounds 2,5-bis(alkylamino)terephthalates 1ac are reported that consist of av ery small p-system (only asingle benzene) but displayefficient red emission in crystals. Crystal 1a having am olecular weight of only 252 gmol À1 shows red emission with the maximum of 620 nm and af luorescence quantum yield of 0.40. The unique emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 50 publications
(23 reference statements)
0
19
0
Order By: Relevance
“…Structurally related SBFs 29 32 also exhibit the characteristics of solvent-independent emission and small dipole moment in the excited-state, which are distinct from typical ICT fluorescence 5 , 16 . To demonstrate the general applicability of our mechanistic model, the same computational protocols were employed to probe the ground- and excited-states of amino–sulfonyl 30 , and amino–ester 31 SBFs (Supplementary Fig. 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…Structurally related SBFs 29 32 also exhibit the characteristics of solvent-independent emission and small dipole moment in the excited-state, which are distinct from typical ICT fluorescence 5 , 16 . To demonstrate the general applicability of our mechanistic model, the same computational protocols were employed to probe the ground- and excited-states of amino–sulfonyl 30 , and amino–ester 31 SBFs (Supplementary Fig. 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…High quality flake-like crystals of 2,5bis(alkylamino)terephthalate derivatives (for chemical structures, see Scheme 4) with coplanar facets featuring ASE behavior were obtained by the same group. 75 The threshold was determined to be 3.1 mJ cm −2 , and the fwhm was 5.9 nm finally, which showed that the crystal was ASE-active. Furthermore, the ASE performances in terms of spectra and intensities of this crystal did not change up to 10 times the measurement at the high pumping intensity of 20.1 mJ cm −2 , which showed its good photostability.…”
Section: ■ Fundamentals Of Esipt Processmentioning
confidence: 95%
“…Single crystals based on structurally simple ESIPT-active organic molecules like 2′-hydroxychalcone derivatives obtained by the solution diffusion approach were observed to show ASE properties by Zhang and his colleagues. , When modified by different substitutes and the same substitute at different positions, slightly different emission wavelengths and ASE properties can be seen. High quality flake-like crystals of 2,5-bis­(alkylamino)­terephthalate derivatives (for chemical structures, see Scheme ) with coplanar facets featuring ASE behavior were obtained by the same group . The threshold was determined to be 3.1 mJ cm –2 , and the fwhm was 5.9 nm finally, which showed that the crystal was ASE-active.…”
Section: Recent Progress In Esipt-based Organic Lasersmentioning
confidence: 98%
“…As a research group within the field of fluorescence-based molecular sensing and bio-imaging [ 13 , 14 , 15 ], we have focused on the development of new SBBF (single-benzene-based fluorophore) derivatives [ 16 , 17 ] and its hybrid materials with inorganic ingredients (e.g., silica, silicon, calcium silicate). The SBBF has an electron-donor (D)-acceptor (A) type dipolar structure ( Figure 1 a), and its emission property could be facilely tunable by changing the functional group at the donor or acceptor site (see Figure 1 b for representative SBBF derivatives) [ 18 , 19 , 20 , 21 , 22 ]. The SBBF has some notable features compared to other well-known organic fluorophores: (i) compact size, (ii) facile wavelength tuning, (iii) bright blue-/green-/red-emission in solid-/solution-state, and (iv) polarity-independent solvatochromic effect.…”
Section: Introductionmentioning
confidence: 99%